Reactivación de detectores de Ge(Li) - Nicolai, J.A.; Giménez, C.R.; Guillermo; Riso, J.M. (Comisión Nacional de Energía Atómica (CNEA), 1981)
Fil:Nicolai, J.A. Comisión Nacional de Energía Atómica (CNEA). República Argentina